2013
DOI: 10.15232/s1080-7446(15)30234-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative housing and feeding systems on the behavior and performance of dairy heifer calves

Abstract: Dedicated to my wonderful parents, Stanley and Leigh Pempek, for their unconditional love and support and for always encouraging me to reach for the stars. They are forever in my heart, my mind, and my determination to succeed. v Acknowledgements Many people have contributed to the success of this project and to the writing of this thesis; I am indebted to them all. First and foremost, I would like to thank my advisor, Dr. Eastridge, for recognizing my abilities and being such a wonderful mentor. I am extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
(129 reference statements)
3
16
1
Order By: Relevance
“…We failed to find a significant difference in solid feed intake in the INDI and PH calves. This result is in accordance with some studies (Chua et al, 2002;Pempek et al, 2013;Bolt et al, 2017;Liu et al, 2019), but in contrast with others (De Paula Vieira et al, 2010;Costa et al, 2015;Jensen et al, 2015;Pempek et al, 2016;Whalin et al, 2018) that found increased solid feed intake in pair-housed calves. We also failed to find a significant difference in growth of INDI and PH calves.…”
Section: Feed Intake and Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…We failed to find a significant difference in solid feed intake in the INDI and PH calves. This result is in accordance with some studies (Chua et al, 2002;Pempek et al, 2013;Bolt et al, 2017;Liu et al, 2019), but in contrast with others (De Paula Vieira et al, 2010;Costa et al, 2015;Jensen et al, 2015;Pempek et al, 2016;Whalin et al, 2018) that found increased solid feed intake in pair-housed calves. We also failed to find a significant difference in growth of INDI and PH calves.…”
Section: Feed Intake and Growthsupporting
confidence: 92%
“…Second, current knowledge on the effect of individual versus pair housing on feed intake and growth is inconclusive. Some studies have found improved solid feed or milk intake in pair-housed calves (De Paula Vieira et al, 2010;Costa et al, 2015;Jensen et al, 2015;Pempek et al, 2016;Whalin et al, 2018), but others have found no improvement (Chua et al, 2002;De Paula Vieira et al, 2010;Pempek et al, 2013;Bolt et al, 2017;Liu et al, 2019). Several investigations have documented improved growth in pair-housed calves (Costa et al, 2015;Jensen et al, 2015;Pempek et al, 2016), but many others were unable to find a positive effect (Chua et al, 2002;Hänninen et al, 2005;De Paula Vieira et al, 2010;Bolt et al, 2017;Whalin et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The artificial rearing of animals represents a combination of emotional (separation from the dam) and nutritional (transition from maternal milk to a commercial milk substitute) stressors in different species [ 3 , 4 ]. It has been suggested that rearing in contact with the mother during the first 12 weeks, even if very limited, may have a positive effect on behavior of heifer when introduced into the dairy herd, as various non-nutritive abnormal oral activities, including self-grooming and tongue playing and cross-sucking have been found to occur in calves fed with a bucket or reared in individual pen [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that when paired calves were lying inside the hutch, they were more often seen lying together in the same hutch (approximately 80% of the time lying inside the hutch), which was also documented in Pempek et al (2013). Calves may have been motivated to maintain physical contact with each other, as shown previously by Holm et al (2002), or to keep warm in the winter (Boe and Havrevoll, 1993).…”
Section: Lying Time and Space Usagementioning
confidence: 64%